Relative Privilege, Risk, and Sense of Community: Understanding Latinx Immigrants' Empowerment and Resilience Processes Across the United States. Issue 3 (22nd December 2020) - Buckingham, Sara L.; Brodsky, Anne E.
Abstract: Latinx immigrants regularly navigate adversity and oppression through resilience and empowerment; however, little research has sought to delineate when, how, and why they may engage in either process. Through the Transtheoretical Model of Empowerment and Resilience, this paper examines how Latinx immigrants living in distinct U.S. contexts interact with their communities. Seventy‐three Latinx immigrants (ages 18 to 70, M  = 40.85, SD  = 13.65) participated in 12 focus groups in Albuquerque, NM; Maricopa County, AZ; Baltimore, MD; and Richmond, VA. Participants had lived in the United States for less than 1 to 39 years ( M  = 14.19, SD  = 8.72) and had varying immigration statuses. Analyses revealed that empowerment and resilience goals diverged by individuals' beliefs in the degree to which external change was vital, possible, and theirs to attempt. Beliefs coincided with the fundamental risk posed, based on the interaction of a context's conditions with an individual's characteristics and sense of community. Results indicate that while resilience is important to navigate risky settings, it may uphold oppressive power structures because it is consistent with the status quo. Interventions to spur external change should involve empowering processes, including facilitating gains in relative privilege and fostering sense of community. Highlights: Immigrants frequently adapt to and withstand adversity and oppression through resilience processes. A belief that external change is possible, needed, and one's to undertake fosters empowerment goals. Resilience and empowerment depend on personal characteristics interacting with context to form risk. An immigrant's sense of community in their new context likely facilitates empowerment processes. Resilience in the absence of empowerment may uphold oppressive power structures.